Biomass Contents Of Chlorella Pyrenoidosa Cultivated In Cobalt-Less Fertilizer-Enriched Saline Water - Widyatama, Awang; Widyatama, Satria Aqilla; Fajry, Zaidan Al; Atmadi, Atmadi; Mulyawati, Ade Heri; Stiawan, Elva (Department of Chemistry, Faculty of Science and Technology, UIN Sunan Gunung Djati Bandung, 2025)
This research aims to provide some information regarding the metabolite contents of the green microalgae Chlorella pyrenoidosa cultivated in designed saline water enriched with affordable commercial fertilizer products in Indonesia. Chlorella pyrenoidosa growth conditions and bioactive compounds were obtained through cultivation and extraction processes. The microalga growth in two different conditions was analyzed based on growth curves between microalgae cultivated in a Guillard f/2 medium and the Cobalt-less fertilizer-enriched saline water. The biomass was profiled using UPLC-QToF-MS and DPPH assay. As a result, Chlorella pyrenoidosa cultures were normally grown on fertilizer-enriched saline water, but with a lower yield performance than those cultivated in the Guillard f/2 medium. The UPLC-QToF-MS result implies that several peptide and lipid derivatives were detected in the harvested microalgal biomass, with the peptide derivatives as the dominant compounds. The limited antioxidant performance was displayed by the untreated biomass extract. This finding implies that several optimizations are still required in the upstream and downstream stages in culturing Chlorella pyrenoidosa by using an uncommon growth medium.